2021
DOI: 10.30880/ijie.2021.13.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Sex Disparity in Satisfaction and Loyalty towards Urban Rail Transit: A Survey of Light Rail Transit (LRT) Passengers in Kuala Lumpur, Malaysia

Abstract: The aim of this study is to explore the effect of sex disparity on passenger satisfaction and loyalty to the light rail transit (LRT) services in Kuala Lumpur, Malaysia. A total of 417 responses from a self-administrated questionnaire were analyzed using non-parametric tests, namely Mann-Whitney U test and Spearman’s correlation test. Based on the Mann-Whitney U test, results showed a significant difference between male and female LRT passengers in terms of their satisfaction and loyalty. In addition, the Spea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Inefficiency of employees, lack of management commitment, train timeliness and bad service at ticketing counters are among the problems cited. In addition, employees should be more empathic, courteous, and professional in their work (Bambale et al, 2020;Ibrahim et al, 2019Ibrahim et al, , 2021Isai et al, 2020). These studies demonstrated the importance of rail employees performing their duties diligently and consistently.…”
Section: Introductionmentioning
confidence: 83%
“…Inefficiency of employees, lack of management commitment, train timeliness and bad service at ticketing counters are among the problems cited. In addition, employees should be more empathic, courteous, and professional in their work (Bambale et al, 2020;Ibrahim et al, 2019Ibrahim et al, , 2021Isai et al, 2020). These studies demonstrated the importance of rail employees performing their duties diligently and consistently.…”
Section: Introductionmentioning
confidence: 83%
“…In this study, the framework testing the American Consumer Satisfaction Index (ACSI) model used the passenger expectation, perceived quality and perceived value constructs as the predictor factors for passenger satisfaction and reuse intention as the consequence of passenger satisfaction. ACSI is a widely recognised model for measuring customer satisfaction in various industries [24,25], including transportation [15,26,27]. ACSI considers multiple factors when evaluating customer satisfaction in the transportation sector, such as passenger expectation, perceived quality, and perceived value, and thus provides a holistic overview of the formation of passenger satisfaction.…”
Section: Stage 2: Artificial Neural Networkmentioning
confidence: 99%
“…The annual ridership of the Kuala Lumpur monorail service declined by 54.8% from 2013 to 2022 [14]. People are more inclined to use private vehicles, such as cars, because they are faster, more reliable and better-suited for fast-paced lifestyles and provide privacy, flexibility, comfort, convenience and independence [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The satisfaction concept in the industrial market motivated transportation researchers to study satisfaction with transportation. Over the past years, many studies have explored the notion of satisfaction with public transport [23,50,[58][59][60][61]. Public transportation authorities deliver an array of offerings, and overall user satisfaction with these services is reflected by how content the ridership is with the public transportation actually delivered.…”
Section: Users' Satisfaction With the Service Quality Attributesmentioning
confidence: 99%